Reformulation of Age Limit for Criminal Liability Child Narcotics Dealer - Thesar Yudi Prasetya; Didik Endro Purwoleksono; Astutik (Universitas Airlangga, 2023)
This article that uses and is based on applicable laws and principles. The legal and regulatory approach is carried out by examining legal provisions, in particular, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, Law Number 35 of 2009 concerning Narcotics, and other related regulations to determine and find out the age of a child before the law. relevant in national criminal law. Based on the above approach, the results of the discussion of this study are: Children in conflict with the law are children who are 12 years old but have not reached the age of 18 who are suspected of committing a crime. This definition was derived from a law known as the Law on the Juvenile Criminal Justice System (UU SPPA), which replaced the law known as the Law on Juvenile Courts. As a result of this definition, it is clear that the Legislature has reached a consensus that the age of eight is an inappropriate age for a person to be held accountable for actions they have committed. In terms of handling narcotics cases, especially children as dealers, the prosecutor's attention is needed to better control the results of investigations conducted by the police so that they can catch perpetrators of child narcotics dealers to uncover a large network of narcotics dealers. Until now there has been no study or regulation that specifically regulates the prosecutor's authority to control the results of investigations by the police to be able to catch perpetrators of child narcotics dealers to uncover the large network of narcotics dealers behind them.